Research on Flow Characteristics of a Variable Mach Number Aerodynamic Test Device by a Rotating Profile. (16th March 2022) - Chen, Zaicheng; Liu, Yang; Bao, Futing; Wei, Ran
Abstract : In the development process of aircraft, it needs to be tested in different incoming flow environments. Therefore, the test equipment that can provide a wide Mach number range and a fast-response flow field has always been a research hotspot. In this paper, a variable Mach number aerodynamic test device by a rotating profile is constructed with a divergent nozzle. The flow field parameters of the device are calculated by numerical simulation. The influence of the initial divergent half-angle of the cubic curve profile and the profile rotation mode on the test area is analyzed by using the flow quality evaluation method. The results show that when the incoming flow Mach number is 1.5 to 3.0, by adjusting the incoming flow Mach number and the expansion ratio of the test device, the Mach number in the test area can change continuously from 3 to 5 and the atmospheric environment at an altitude of 11 km to 20 km can be simulated. The test device composed of the cubic curve profile with the same initial divergent half-angle as the original straight line has a better flow quality. The both-side rotation mode can ensure the symmetry of the flow direction better than the one-side rotation mode.